Cultivo da microalga Pseudokirchneriella subcapitata em escala de bancada utilizando meio contaminado com metais pesados - Ansilago, Mônica; Ottonelli, Franciéli; De Carvalho, Emerson Machado [UNESP] (FapUNIFESP (SciELO), 2016)
This study evaluated the growth of microalgae Pseudokirchneriella subcapitata amid growing alternative NPK (20:05:20) contaminated with heavy metals. The first treatment consists of the control without addition of dopant, while others were infected with AlCl3, FeSO4 e ZnSO4 and the three metals. Of the results obtained, the control was the only one that showed continued positive growth, while all metal-containing treatment had a higher density and a higher rate of exponential growth. Treatment contaminated with ZnSO4 had the lowest production potential. Despite the figures, all treatments showed positive growth at the end of the test, so it is possible to assign a high potential for microalgae production in water contaminated by metals.
Cultivation of microalgae pseudokirchneriella subcapitata in bench scale using medium contaminated with heavy metals
Keywords: Algal density; Bioremediation; Chlorophyceae; Exponential growth; Wastewater